The rights of minority cultures - Kymlicka, Will (Oxford, [England] Oxford University Press, 1995)
This volume collects together the most important contemporary articles on the rights of minority cultures. While drawing on particular case studies, the articles focus on the more general theoretical and normative issues raised by the accommodation of cultural differences. The authors represented in this volume come from a variety of countries and disciplines, and reflect a wide range of opinion. The book explores the nature and value of cultural membership, models of cultural pluralism, individual and group rights, minority representation, immigration, and secession. A new and substantial essay by Will Kymlicka outlines the major issues and perspectives raised in the articles, and places them in the context of contemporary debates in political theory. The volume also includes a guide to further reading for students and researchers working in the field. Compiled by the leading political philosopher of his generation, Will Kymlicka's Rights of Minority Cultures will be of great interest to scholars of political theory, political philosophy, policy studies, ethnic studies, and law.
Includes bibliographical references (pages [375]-382) and index.
Keywords: Minorities -- Civil rights